Changes of Hamza in the Khuzestani Written Arabic:The Case of Muhammad Atyyehâs Book of Poems - Mohammad Javad Hesavi (دراسات فی اللغه العربیه و آدابها)
Elegiac poetry written about the Ahlolbeit (the Holy Prophetâs Household) in Khuzestani Arabic is a rich folklore source. This poetic genre is beautiful and appealing and almost comprehensible for its audience. However, it is mysteriously difficult for all to read. This often leads to misunderstandings. The incomprehensibility of Khuzestani Arabic may be due to different reasons. For example, little attention is paid to spelling rules in this dialect, there are no consistent rules for spelling and the majority of those in publishing and editorial work are not familiar with the alphabet of this dialect therefore, they make spelling errors. Hamza is one of the sounds which is prone to errors, especially the conjunctive hamza so, it may be represented by different symbols in different books or even in one single book. This character has been altered in different forms in Khuzestani Arabic including addition, omission, replacement with another letter, word blending, and the use of an alternative word without hamza. Since the speakers of this dialect are not familiar with its writing system, it will be difficult for them and non-native speakers to read and understand. This article seeks to investigate the changes that hamza goes through in Khuzestani dialect and tries to clarify the ways of writing this character so that it has a consistent written form, typographical errors are distinguishable from the spelling ones, the gap between Khuzestani dialect and the standard Arabic is narrowed and it is comprehensible for all. Furthermore, the poets of this region, particularly poets of Ahlolbeit will be known worldwide. This research is primarily focused on Muhammad Atyyehâs book of poems.